Algorithmic Enclaves and Political Sophistication: A Structural Equation Modeling (SEM) of Gen Z’s Voting Behavior in Indonesia’s 2024 Election - Arya Ganendra; Danila Adi Sanjaya; Ifah Shandy (HM Publisher, 2025)
The 2024 Indonesian General Election marked a paradigm shift in democratic engagement, with Generation Z emerging as the primary electoral demographic. This study investigates the impact of algorithmic enclaves—AI-curated digital spaces—on the voting behavior of young voters. It specifically explores how these enclaves influence political sophistication and whether they facilitate informed decision-making or exacerbate affective polarization in a transitioning democracy. Utilizing a quantitative approach, this research employs Structural Equation Modeling (SEM) to analyze a nationwide dataset of 1,200 Gen Z respondents aged 17–27. The model tests the structural relationships between Algorithmic Awareness, Echo Chamber Exposure, and Political Sophistication as determinants of Voting Behavior. The SEM analysis demonstrates that Algorithmic Enclaves have a significant direct effect on voting preferences (Beta = 0.48, p < 0.001). Crucially, Political Sophistication serves as a partial mediator; however, its efficacy is contingent upon Algorithmic Awareness. For voters with low awareness, enclaves significantly narrowed political horizons, whereas high awareness acted as a moderating buffer. In conclusion, the study concludes that algorithmic curation has redefined the Indonesian political landscape. To safeguard democratic integrity, it is imperative to transition from basic digital access to advanced algorithmic literacy.